In Vitro Antibacterial and Antioxidant Activities of Roasted and Green Coffee Beans Originating from Different Regions of Ethiopia. (25th August 2020) - Tasew, Tsedale; Mekonnen, Yalemtsehay; Gelana, Tegenu; Redi-Abshiro, Mesfin; Chandravanshi, Bhagwan Singh; Ele, Estifanos; Mohammed, Ahmed Mustefa; Mamo, Hassen
Abstract : Coffee is among the most traded commodities and consumed beverages worldwide primarily for its stimulating effects. Moreover, coffee is known to contain various bioactive compounds with significant health benefits including antibacterial and antioxidant activities. However, Ethiopia as the origin of coffee and producer and exporter of varieties of Coffea arabica has made little study on the health aspects of this beverage. The aim of this study was to examine the antibacterial and antioxidant activities and content of coffee samples from different localities of Yorgacheffe and Jimma; and roasted, ground, and packed samples purchased from a coffee shop in Addis Ababa. Medium-roasted-boiled and lyophilized coffee extracts were tested on eight gram-negative and gram-positive bacterial strains. The agar-well diffusion method was used to test the extracts determining the minimum inhibitory and bactericidal concentrations. For coffee antioxidant activity and content, light-roasted (both field and shop samples) and green coffee bean extracts were tested using the free radical 2.2-diphenyl-l-pict1hydrazyl (DPPH) IC50 percent inhibition protocol. The samples showed strong antibacterial and antioxidant activity and substantial antioxidant content. Significant variation was noted in the antibacterial activities of the different coffee samples. Moreover, the growth-inhibitory strength of each coffee sample was variable for different test bacteria. A coffee sample with the best antibacterial activity had also the highest antioxidant activity/content. The shop coffee had the lowest bioactivity. The observed variations in the antibacterial and antioxidant activities among the samples probably indicate the diversity of the Ethiopian coffee related, among other factors, to the coffee plant genetics and agroecology.